Temperature dependent radiative and non-radiative recombination lifetimes of luminescent amorphous silicon oxynitride systems - Zhang, Pengzhan; Liu, Xinyu; Zhang, Ling; Wang, Danbei; Wu, Kongpin; Wang, Sake (Frontiers in Physics, 2024)
In our previous work, we deeply researched the absolute photoluminescence (PL) quantum yields of luminescent modulating a-SiNxOy films with various N/Si atom ratios under different measurement temperatures. In this work, we further systematically studied the temperature dependent kinetic processes of radiative and non-radiative recombinations in a-SiNxOy systems in the visible light range. First, we investigated the structure of a-SiNxOy films and obtained the concentrations of both trivalent Si and N-Si-O defects related dangling bonds through XPS, FTIR and EPR measurements. Then we further tested the transient fluorescence attenuation of a-SiNxOy films detected at different emission wavelengths. We found that the PL lifetimes of a-SiNxOy films vary with the change of N-Si-O defect state concentrations, which is different from the typical PL decay characteristics of band tail related a-SiNx films previously reported. By combining the resulting PL IQE values with the ns-PL lifetimes, we further intensively redetermined the radiative and non-radiative recombination lifetimes of a-SiNxOy systems. The related radiative recombination rates were obtained (kr∼108 s−1), which can be compared to the results in the direct band gap.